Gut Microbiota: Target for Modulation of Gut-Liver-Adipose Tissue Axis in Ethanol-Induced Liver Disease. (20th May 2022) - Patel, Dhara; Sharma, Dixa; Mandal, Palash
Abstract : Consumption of alcohol (ethanol) in various forms has been an integral part of human civilization. Since ages, it also has been an important cause of death and health impairment across the globe. Ethanol-mediated liver injury, known as alcoholic liver disease (ALD), is caused by surplus intake of alcohol. Several studies have proposed the different pathways that may be lead to ALD. One of the factors that may affect the cytochrome P450 (CYP2E1) metabolic pathway is gut dysbiosis. The gut microbiota produces various compounds that play an important role in regulating healthy functions of distal organs such as the adipose tissue and liver. Dysbiosis causes bacteremia, hepatic encephalopathy, and increased intestinal permeability. Recent clinical studies have found better understanding of the gut and liver axis. Another factor that may affect the ALD pathway is dysfunction of adipose tissue metabolism. Moreover, dysfunction of adipose tissue leads to ectopic fat deposition within the liver and disturbs lipid metabolism by increasing lipolysis/decreasing lipogenesis and impaired glucose tolerance of adipose tissue which leads to ectopic fat deposition within the liver. Adipokine secretion of resistin, leptin, and adiponectin is adversely modified upon prolonged alcohol consumption. In the combination of these two factors, a proinflammatory state is developed within the patient leading to the progression of ALD. Thus, the therapeutic approach for treatments and prevention for liver cirrhosis patients must be focused on the gut-liver-adipose tissue network modification with the use of probiotics, synbiotics, and prebiotics. This review is aimed at the effect of ethanol on gut and adipose tissue in both rodent and human alcoholic models.